Divorce and Domestic Violence Among Syrian Refugees in Germany - Al Ajlan, Ahmad (Journal of interpersonal violence, 2022)
In recent literature, there are no academic studies on divorce and domestic violence among Syrian refugees in Germany. To contribute to filling this gap, the current study addresses the question: What are the main causes of divorce and domestic violence among Syrian refugees in Germany, and how are these two phenomena interrelated? The present study is based on 14 qualitative interviews with divorced Syrian refugee men and women in Germany, all of them are Muslim with different economic backgrounds from urban and rural areas in Syria and got divorced shortly after their arrival to Germany. The data were analyzed and coded following Mayring?s guidelines for content analysis. The findings suggest that domestic violence results from conflicts of interest in marriage and divorce between Syrian refugee men and women. The present study uses the economic theory of marriage and divorce by Cary Becker to show how Syrian refugee women?s ?gains? of divorce in Germany exceed the ?gains? of remaining married and how that leads them to divorce their husbands. In contrast, divorce is a heavy loss for Syrian refugee men. In addition, it shows how this conflict of interest results in domestic violence, by which the men resist their wives? eagerness to divorce and interpret the marital relationship according to Sharia law and Arabic traditions in order to keep their old patriarchal authority. However, this interpretation is inapplicable and criminalized by the German family legislation, and unwanted by their wives. The findings, through the example of Syrian refugees in Germany, imply that the causes of divorce and domestic violence among refugees in some regards are unique in comparison with natives and migrants. That means that we need more studies on this topic in different socio-cultural contexts.